E-OFFICE PADA KANTOR CAMAT MESTONG KABUPATEN MUARO JAMBI BERBASIS WEB: Mestong Sub-district Office, Muaro Jambi Regency, E-Office, Archives, Archives System - Nilawati, Nilawati; Riswan, Riswan; Shinta, Shinta (LP2M Universitas Nurdin Hamzah, 2025)
The purpose of this study was to create a system at the Mestong District Office of Muaro Jambi Regency to make it easier to access or store archival data for incoming and outgoing letters. The author collects data using research methods in the form of field research (Field Research), observation (Observation), interviews (Interview), and documentation (documentation). The results showed that the management of incoming and outgoing mail archive data still uses a manual system, namely by recording the letter data in the agenda book then the letters are placed in a special mail file cabinet without any backup data... The solution proposed by the author is to design and build a website-based system for archiving incoming and outgoing mail. The design of this application is built using the PHP programming language and MySQL DBMS so as to produce the desired website program. The results of this study are expected to be developed by further researchers, because in this study there are still many shortcomings.